Feasibility and comparison of laparoscopic laser speckle contrast imaging to near-infrared display of indocyanine green in intraoperative tissue blood flow/tissue perfusion in preclinical porcine models - Nwaiwu, Chibueze A.; Buharin, Vasiliy E.; Mach, Anderson; Grandl, Robin; King, Matthew L.; Dechert, Alyson F.; O’Shea, Liam; Schwaitzberg, Steven D.; Kim, Peter C. W. (Surgical endoscopy, 2023)
Objective To determine if laser speckle contrast imaging (LSCI) mitigates variations and subjectivity in the use and interpretation of indocyanine green (ICG) fluorescence in the current visualization paradigm of real-time intraoperative tissue blood flow/perfusion in clinically relevant scenarios. Methods De novo laparoscopic imaging form-factor detecting real-time blood flow using LSCI and blood volume by near-infrared fluorescence (NIRF) of ICG was compared to ICG NIRF alone, for dye-less real-time visualization of tissue blood flow/perfusion. Experienced surgeons examined LSCI and ICG in segmentally devascularized intestine, partial gastrectomy, and the renal hilum across six porcine models. Precision and accuracy of identifying demarcating lines of ischemia/perfusion in tissues were determined in blinded subjects with varying levels of surgical experience. Results Unlike ICG, LSCI perfusion detection was real time (latency < 150 ms: p < 0.01), repeatable and on-demand without fluorophore injection. Operating surgeons ( n = 6) precisely and accurately identified concordant demarcating lines in white light, LSCI, and ICG modes immediately. Blinded subjects ( n = 21) demonstrated similar spatial–temporal precision and accuracy with all three modes ≤ 2 min after ICG injection, and discordance in ICG mode at ≥ 5 min in devascularized small intestine ( p < 0.0001) and in partial gastrectomy ( p < 0.0001). Conclusions Combining LSCI for near real-time blood flow detection with ICG fluorescence for blood volume detection significantly improves precision and accuracy of perfusion detection in tissue locations over time, in real time, and repeatably on-demand than ICG alone. Graphical abstract